Violent victimization and perceptions of safety: Experiences of First Nations, Métis and Inuit women in Canada - Heidinger, Loanna (Juristat, 2022)
Experiences of First Nations, Métis and Inuit women in Canada: Highlights * Violence against Indigenous peoples reflects the traumatic and destructive history of colonialization that impacted and continues to impact Indigenous families, communities and Canadian society overall. * Violent victimization is defined in the 2018 Survey of Safety in Public and Private Spaces (SSPPS), as a physical assault (an attack, a threat of physical harm, or an incident with a weapon present) or a sexual assault (forced sexual activity or attempted forced sexual activity). * Results from the SSPPS indicate that more than six in ten (63%) Indigenous women have experienced physical or sexual assault in their lifetime. * Almost six in ten (56%) Indigenous women have experienced physical assault while almost half (46%) of Indigenous women have experienced sexual assault. First Nations, Métis and Inuit (Indigenous) peoples are diverse and have unique histories, languages, cultural practices and spiritual beliefs. [...]Indigenous women may face unique barriers to reporting experiences of violent victimization or seeking help following victimization, including a lack of access to culturally appropriate resources, inaccessibility of support services, a general distrust of law enforcement, and perceived lack of confidentiality in the justice system (Truth and Reconciliation Commission of Canada 2015). [...]homicide data highlights the prevalence and characteristics among homicide of Indigenous women in Canada.
Place: Ottawa